A strategy to reduce illicit drug use is effective in elite Australian football. Issue 13 (14th August 2012) - Harcourt, Peter R; Unglik, Harry; Cook, Jill L
Abstract : Background: The World Anti-Doping Agency (WADA) prescribes that drug testing is conducted in sports competitions to detect drug use in athletes. This testing includes performance-enhancing drugs as well as illicit substances such as marijuana, amphetamines and cocaine. Illicit drugs are tested for on match days but not on non-match days. Some athletes are known to use illicit substances for recreational purposes, away from competition times and this poses a serious health and welfare issue not addressed by the usual sport drug testing regimes. This paper reports the results of the first 7 years of an illicit drug-testing programme that included non-match day testing in the elite Australian Football competition, the Australian Football League (AFL). Methods: Players in the AFL were tested for illicit drugs both in-competition and out-of-competition. Players were selected for illicit substance tests either randomly or targeted based on previous test history or time since previous test. The number of tests conducted was increased each year from 2005 to 2011 and testing was focused on high-risk times during non-competition periods. Results: There were no positive match day tests. There was a significant reduction in positive tests (19–6) for illicit drugs during non-competition periods over the 7 years (p<0.0001). The reduction in positive tests may be related to player education, the greater number of tests conducted and the harm minimisation approach of the illicit drug policy. Conclusions: An illicit drugs programme using a harm minimisation strategy can work effectively alongside a sport's WADA compliant Anti-Doping Code.